Корректность модифицированной модели материальной точки в теории полета снаряда - Коносевич, Б.И.; Коносевич, Ю.Б. (Механика твердого тела, 2015)
Для описания движения артиллерийского снаряда в воздухе широко используется система дифференциальных уравнений, которая получается из исходной “точной” системы путем линеаризации аэродинамических сил и моментов по углу атаки и путем дополнительной линеаризациипоуглумежду вектором скорости центрамасс снарядаивертикальной плос костью (l-система). Усреднение уравнений поступательного движения и продольного вращения в l-системе по обеим фазам собственных угловых колебаний оси симметрии снаряда приводит к системе дифференциальных уравнений, которая описывает модифицированую модель материальной точки (m-система). При помощи методов малого параметра получена оценка погрешности решения m-системы по сравнению с решением l-системы при одинаковых начальных условиях для переменных поступательного движения и продольного вращения. Установлена малость этой погрешности, что и является обоснованием корректности модифицированной модели материальной точки. As the starting point, the system of differential equations of motion of the shell is taken, which is obtained from the original “accurate” system by holding the linear terms of series expansions of aerodynamic forces and moments in powers of the total angle of attack, and by additional linearization with respect to the angle between the velosity of the centre of mass and the vertical plane (l -system). It consists of the subsystem of equations of translational motion and axial rotation, and of the subsystem of equations of angular motion of the symmetry axis of the shell. Averaging the first subsystem in both natural phases of angular oscillatios leads to the approximate system of differential equations of the translational motion and axial rotation of the shell, which describes its modified point-mass model as applied to l-system (m-system). With use of small-parameter methods, an estimate is obtained for the difference between the solution of l -system with given initial conditions and the solution of m-system with the same initial conditions for the variables of translational motion and axial rotation. This analytical evaluation is built in such a way that it corresponds with certain numerical estimates for components of the translational motion and axial rotation.